Treatment of Leather Industry Wastewater and Recovery of Valuable Substances to Solve Waste Management Problem in Environment - Kannaujiya M.C.; Mandal T.; Mandal D.D.; Mondal M.K. (My University, 2025)
Every leather industry produces a large quantity of wastewater having enormous amount of pollutants which have a deleterious effect on the environment drastically if it is discharged without appropriate treatment. The tanning processes are responsible for the discharge of uncontrolled COD, BOD, TDS, Cr (III), chlorides, sulphates, and other heavy metals. This study provides a review of the treatment of leather wastewater involving physical treatment, electrocoagulation, adsorption, chemical precipitation, ozonation, electro-oxidation, photocatalytic ozonation, Fenton oxidation, biochemical/biological treatment, and hybrid treatment processes. It is clear from the study of some other papers that chemical or biological treatment followed by membrane separation has the potential capability to remove the harmful contaminants from tannery wastewater. Researchers also reported that the tannery industrial solid waste used after removal of chromium has a good amount of minerals (P and K) which can be further used for several purposes including as fertiliser. © Springer Nature Singapore Pte Ltd. 2019.